Cognitive behavioral therapy for depression and anxiety of Parkinson's disease: A systematic review and meta-analysis. (May 2020) - Zhang, Qi; Yang, Xia; Song, Huimin; Jin, Yi
Abstract: Object: To systematically evaluate the effects of cognitive behavioral therapy on anxiety and depression symptoms of patients with Parkinson's disease. Methods: Four electronic databases (MEDLINE, EMBASE, CINAHL and the Cochrane Library) to May 2019 were searched. The outcome measure of interest was anxiety and depression. Randomized controlled trials or quasi-experimental studies were included in our review. The included individual study's risk of bias were assessed with the Cochrane Collaboration's tool. And the meta-analyses were performed. Results: A total of 7 studies were included in the meta-analysis with 191 patients. Meta-analysis indicated observed beneficial effects of cognitive behavioral therapy in the reduction of anxiety and depression for individuals with Parkinson's disease. Conclusions: This meta-analysis revealed that cognitive behavioral therapy is effective in relieving depression and anxiety of patients with Parkinson's disease. Medical workers could apply cognitive behavioral therapy into daily routine cares for patients with Parkinson's disease. More studies with high quality and follow-up assessment on this topic are still required. Highlights: This is the first mate-analysis to explore the effects of CBTon depression and anxiety for PD. Our findings provides evidence to support that CBT is a promising therapy that contributes to reduction of anxiety and depression. Medical workers could apply CBTinto daily routine managements of PD.